"It's a lonely battle": A qualitative study of older adult Canadians' experiences with chronic obstructive pulmonary disease medication adherence and support. (January 2023) - Skerry, Leanne; Kervin, Emily; Freeze, Tracy A.; Brillant, Andrew; Woodland, Jennifer; Hanson, Natasha
Background: Medication adherence is critical for optimal management of chronic obstructive pulmonary disease (COPD) and is influenced by patient, treatment and societal factors. Currently, little is known about the patient perspectives of older adult Canadians with COPD regarding medication adherence. Therefore, the purpose of this study was to explore the lived experiences of older Canadian adults with COPD regarding medication adherence and management. Methods: Semi-structured interviews were conducted with 20 community-dwelling older adults with COPD, and iterative thematic analysis was performed. Results: Six themes emerged from these data: (1) continuity of care, (2) importance of pharmacy for information and care, (3) medication self-management, (4) "there needs to be more information, " (5) drug costs a concern and (6) "it's a lonely battle." Conclusion: Findings suggested a need for improved continuity of care, disease-related information provision and means of addressing psychosocial needs. Holistic approaches to patient education and self-management, with consideration for varying health literacy, are needed.